Cho `a + b + c = 0` Chứng minh `M = N= P` biết : `M = a (a + b) (a + c), N = b (b + c) (b + a), P = c (c + a) (c + b)`

Question

Cho `a + b + c = 0` Chứng minh `M = N= P`
biết : `M = a (a + b) (a + c), N = b (b + c) (b + a), P = c (c + a) (c + b)`

in progress 0
Eliza 5 tháng 2021-07-15T09:39:54+00:00 2 Answers 7 views 0

Answers ( )

    0
    2021-07-15T09:41:02+00:00

    Đáp án:

     

    Giải thích các bước giải:

        Ta có : a+b+c=0
    ⇔ -c= a+b
         -b = a+c
         -a= b+c
    Ta có :  M = a(a+b)(a+c) (1)
    Thay -c = a+b và  -b = a+c vào (1) ta đc:
        M= a(-c)(-b)
           = abc (*1)
    Ta có: N= b(b+c)(b+a)  (2) 
       Thay  -a = b+c và -c= a+b vào (2) ta đc :
            N= b(-a)(-c)
               = abc (*2)
    Ta có:  P= c(c+a)(c+b)  (3) 
         Thay   -b  = a+c  và  -a= b+c vào (3) ta đc :
              P= c(-b)(-a)
                = abc (*3) 
    Từ (*1)(*2)(*3) ⇒ M=N=P (=abc) 
    Vậy M=N=P

             
       

    0
    2021-07-15T09:41:48+00:00

    Đáp án + Giải thích các bước giải:

    Ta có:

         a+b+c= 0 

    ⇒  a + b = -c           (chuyển vế)

          a + c = -b

          b + c = -a

    Khi đó ta lại có:

     M = a(a+b)(a+c) = a(-c)(-b) = abc.  (1)

     N = b(b+c)(b+a) = b(-a)(-c) = abc    (2)

     P = c(c+a)(c+b) = c(-b)(-a) = abc        (3)

    Từ (1), (2), (3) suy ra: M=N=P

    Chúc bn hok tốt!

          

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )